2011
DOI: 10.1186/1744-859x-10-28
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of psychiatric symptomatology reported by health professionals working in medical settings in Greece

Abstract: BackgroundPsychological distress in healthcare workers may vary across different specialties. The purpose of this study was to investigate the differences in the rate of anxiety and depression between medical and mental healthcare workers.MethodsThe sample was randomly selected and consisted of 229 workers from the medical health sector and 212 from the mental health sector, aged 39.8 ± 7.9 years old. Health workers from University and General Hospitals from all over Greece participated in the study. The Greek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…According to previous literature [ 1 , 3 , 11 , 16 ] we reported PTSD rates among health professionals operating in the emergency in Italy higher than those reported, despite with different methodological approaches, in the general population [ 6 , 33 ]. The rates we found are in the range of prior works developed worldwide [ 3 , 14 , 34 , 35 ], but appear to be in the higher range of prior works on nurses and health care workers operating in the emergency services across Europe, where PTSD prevalence rates ranging between 10 and 21% have been reported [ 8 , 16 , 34 , 36 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…According to previous literature [ 1 , 3 , 11 , 16 ] we reported PTSD rates among health professionals operating in the emergency in Italy higher than those reported, despite with different methodological approaches, in the general population [ 6 , 33 ]. The rates we found are in the range of prior works developed worldwide [ 3 , 14 , 34 , 35 ], but appear to be in the higher range of prior works on nurses and health care workers operating in the emergency services across Europe, where PTSD prevalence rates ranging between 10 and 21% have been reported [ 8 , 16 , 34 , 36 ].…”
Section: Discussionmentioning
confidence: 88%
“…Psychological distress in health care workers may vary across different specialties but increasing evidence highlights that staff operating in emergency planning, such as doctors, nurses, and paramedics, to be at high risk for PTSD [ 1 ]. Emergency departments, in fact, may be challenging because of frequent unpredictability of daily work cases, coping with the acute phase of most disorders, including traumatic incident exposure, frequently facing patients’ and their families’ expectations in unexpected and acute critical cases/situations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies undertaken in medical settings generally report twice the rates of MDD compared to those undertaken in the community. 13 One trial in the USA undertaken among adolescents attending primary care clinics reported a baseline prevalence of probable depression in 26%; 14 a recent study among adolescent cancer patients attending care in Uganda reported a prevalence of MDD in 26%. 15 Reported risk factors for adolescent MDD in the sub-Saharan African setting include female gender, living in a child-headed household, orphanhood, living with a single parent, low parental educational attainment, chronic physical illness, alcohol and drug abuse.…”
Section: Introductionmentioning
confidence: 99%